Situation Report: Hungary, 15 July 1988 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. CC Meeting Works Out Plan for Political Reforms / by Alfred Reisch Political Reform: The National Council of Trade Unions / by Zoltan Barany Head of National Bank Replaced / by Karoly Okolicsanyi Ilona Tatai: The Politburo's New Expert on Management / by Karoly Okolicsanyi Rude Pravo Reports on Rift between Hungary and Romania Western Press Coverage of the Hungarian-Romanian Conflict / by Kevin Devlin